The movement of involucral bracts of Syngonanthus elegans (Eriocaulaceae-Poales): Anatomical and ecological aspects - Oriani, Aline [UNESP]; Scatena, Vera Lucia [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2009)
Syngonanthus elegans flowers are distributed in capitula whose involucral bracts open and close in a diurnal rhythm. The anatomy of these bracts was studied to understand how such movements occur and how it influences reproductive ecology of the species. The involucral bracts have a single layered epidermis composed of thick-walled cells on the abaxial surface, which are responsible for the movement. Since they are hygroscopic, these cells swell when they absorb water from the surrounding environment, causing the bracts to bend and the capitula to close. In natural conditions, the capitula open by day, when temperature increases and the relative air humidity decreases, and close at night, when temperature decreases and the relative air humidity increases. The involucral bracts may thus protect the flowers from abiotic factors, exposing them only at the time of the day when temperature is higher and insects are more active, favoring pollination by small insects. The closed capitula do not only protect the flowers, but they also function as a shelter for floral visitors as Brachiacantha australe (Coccinellidae) and Eumolpini sp. (Chrysomelidae). These small Coleoptera pollinate the flowers of S. elegans during the day and remain within the closed capitula during the night, in a possible mutualistic relationship. (C) 2008 Elsevier GmbH. All rights reserved.
Keywords: Syngonanthus elegans; Eriocaulaceae; Involucral bracts; Hygroscopic movement; Pollination biology; Diurnal inflorescence opening